Understanding prejudice and discrimination - Plous, Scott (Boston : McGraw-Hill, 2003)
This anthology, edited by Scott Plous, is designed as a supplementary text for a course in prejudice and discrimination. It represents a collection of readings edited, adapted, or revised specifically for this anthology - several of which have never been published before. The surveys, experiments, and other studies included are set in a cultural and historic context that includes personal narratives, news stories, legal decisions, poetry, social commentary, and assorted other material. Several readings come from people on the receiving end of prejudice (often referred to as "targets" of prejudice.) Interdisciplinary in its selection of readings, this anthology is an unusual combination of readings in which laboratory studies and national opinion polls appear side-by-side with U.S. Supreme Court decisions and New York Times articles
Section I. Homo Stereotypus: Wired for TroubleThe Psychology of Prejudice, Stereotyping, and Discrimination: An Overview - Scott PlousWho Is Black? One Nation's Definition - F. James DavisSection II. StigmaNo Pity: People with Disabilities Forging a New Civil Rights Movement - Joseph P. ShapiroIn Europe, Outcry Is Loud Over a Sport Called Dwarf-Tossing - Paul HempAvoidance of the Handicapped: An Attributional Ambiguity Analysis - Melvin L. Snyder, Robert E. Kleck, Angelo Strenta, and Steven J. MentzerCiting Intolerance, Obese People Take Steps to Press Cause - Carey GoldbergRace and the Schooling of Black Americans - Claude SteeleThe Stereotype Trap - Sharon BegleySection III. Racism ThenThe Hottentot Venus - Stephen Jay GouldThe Use of Blacks for Medical Experimentation and Demonstration in the Old South - Todd L. SavittComing of Age in Mississippi - Anne MoodyThe American Concentration Camps: A Cover-Up Through Euphemistic Terminology - Raymond Y. OkamuraSection IV. Racism NowFive Myths About Immigration: The New Know-Nothingism - David ColeOnce Appalled by Race Profiling, Many Find Themselves Doing It - Sam Howe VerhovekRace to Incarcerate - Marc MauerA Computer Diagnosis of Prejudice - Erica GoodeService with a Sneer - Howard KohnWhite Privilege: Unpacking the Invisible Knapsack - Peggy McIntoshReflections of Affirmative Action Goals in Psychology Admissions - James Amirkhan, Hector Betancourt, Sandra Graham, Steven Regeser López, and Bernard WeinerTen Myths About Affirmative Action - Scott PlousSection V. SexismListening - Sey ChasslerAn Ambivalent Alliance: Hostile and Benevolent Sexism as Complementary Justifications for Gender Equality - Peter Glick and Susan T. FiskeThe Deadly Serious Game of the Beauty Pageant - Sandra McElwaineInfluence of Popular Erotica and Judgments of Strangers and Mates - Douglas T. Kenrick, Sara E. Gutierres, and Laurie L. GoldbergMale Epithets for Ethnic Women in Historical American Slang - Irving Lewis AllenDetecting and Labeling Prejudice: Do Female Perpetrators Go Undetected? - Robert S. Baron, Mary L. Burgess, and Chuan Feng KaoSection VI. Anti-SemitismThe Destruction of the European Jews: Dehumanization and Concealment - Raul HilbergAntisemitism in America - Leonard DinnersteinWhile Six Million Died: A Chronicle of American Apathy - Arthur D. MorseADL 2000 Audit of Anti-Semitic Incidents - Anti-Defamation LeagueSection VII. Genocide in AmericaNaming Our Destiny: Toward a Language of American Indian Liberation - Ward ChurchillLet's Spread the "Fun" Around: The Issue of Sports Team Names and Mascots - Ward ChurchillBattle Rages Over a 5-Letter Four-Letter Word - Eric SchmittNew Prosperity Brings New Conflict to Indian Country - Timothy EganSection VIII. HeterosexismBiblical Verse: Is It a Reason or an Excuse? - Deb PriceViolence Toward Homosexuals - Karen Franklin and Gregory M. HerekIs Homophobia Associated with Homosexual Arousal? - Henry E. Adams, Lester W. Wright, Jr., and Bethany A. LohrTransgender Identities: Like Stars in the Sky - Vanessa BairdSuit Over Estate Claims a Widow Is Not a Woman - Jodi WilgorenSection IX. Making ConnectionsPeace Is Every Step: The Path of Mindfulness in Everyday Life - Thich Nhat HanhPrejudice as a Generalized Attitude - Gordon W. AllportEnvironmental Justice for All - Robert D. Bullard and Beverly H. WrightSection X. Reducing PrejudiceReducing the Expression of Racial Prejudice - Fletcher A. Blanchard, Teri Lilly, and Leigh Ann VaughnLong-Range Experimental Modification of Values, Attitudes, and Behavior - Milton RokeachThe Role of Empathy in Improving Intergroup Relations - Walter G. Stephan and Krystina FinlayThe Challenge of Aversive Racism: Combating Pro-White Bias - Samuel L. Gaertner, John F. Dovidio, Brenda S. Banker, Mary C. Rust, Jason A. Nier, Gary R. Mottola, and Christine M. WardMartin Luther King Explains Nonviolent Resistance - Martin Luther King, Jr.Appendix: Animals as an OutgroupIs There Such a Thing as Prejudice Toward Animals? - Scott PlousGaps in the Mind - Richard DawkinsUnheard Voices: Institutionalized Prejudice Toward Animals in the U.S. Meat Industry - Gail A. EisnitzGlossariesSource Notese Notese Notes
A compilation of readings from a broad range of scholarly disciplines, most edited, adapted, or revised for this anthology and several never published before
The text is supported by a variety of instructional materials, including a web site offering interactive exercises and demonstrations, streaming video clips, and other resources
Keywords: predrasude; diskriminacija